EFFECTS OF ALMOND MEAL (TERMINALIA CATAPPA) BASED DIETS ON NUTRIENT UTILIZATION, GROWTH AND HEMATOLOGY OF LABEO ROHITA FINGERLINGS - S. M. Hussain; S. Nisar; M. Jamil; F. Bashir; M. Z. ul H. Arslan; S. Tabassum; B. Ahmad; S. Ahsan; A. Sharif (Journal of Animal and Plant Sciences, 2021)
Nutrient utilization, hematological indices and growth performance of Labeo rohita fingerlings were examined while substituting fish meal with almond meal-based diet. Five diets were prepared by substituting different levels such as 0%, 20%, 40%, 60%, 80% and 100% of fish meal with almond meal in diets. Test diets were allocated to each fish group by using completely randomized design (CRD). In triplicate tanks, fifteen L. rohita fingerlings were kept and fed at 5% of their body weight. Growth indices such as weight gain (%), feed conversion ratio (FCR) and standard growth rate (SGR) were evaluated using standard formulae. Nutrient utilization was determined by proximate analysis of feces. There was significant difference (p≤0.05) among hematological indices and growth performance of fingerlings fed 40% almond meal-based diet and control diet. By increasing almond meal in diets more than 40%, the hemoglobin and RBCs of fish indicated a significant (p≤0.05) inverse correlation. The outcomes of present study revealed that replacement of fish meal by almond meal in fish feed is cost effective with significant improvement in growth response, nutrient digestibility and hematology.
Keywords: Replacement; growth rate; hemoglobin; nutrient utilization; plant proteins